Experimental and modeling study of proton and copper binding properties onto fulvic acid fractions using spectroscopic techniques combined with two-dimensional correlation analysis. (January 2020) - Li, Tingting; Song, Fanhao; Zhang, Jin; Tian, Shijie; Huang, Nannan; Xing, Baoshan; Bai, Yingchen
Abstract: Fulvic acid (FA) significantly influences the bioavailability and fate of heavy metals in environments, while its acid-base characters and metal binding processes are still unclear. Here, spectroscopic techniques combined with multiple models (e.g., NICA-Donnan model) and two-dimensional correlation spectroscopy (2D COS) were applied to explore the proton and copper binding properties of FA sub-fractions (FA3 -FA13 ). The charge densities, average contents of carboxylic and phenolic groups, average dissociation constants p Ka 1 and p Ka 2 of sub-fractions ranged 0–16 meq∙g∙C −1, 5.03–9.58 meq∙g∙C −1, 2.52–4.67 meq∙g∙C −1, 4.15–4.33 and 8.52–9.72, respectively. FA sub-fractions had a relatively narrow distribution of carboxyl group and a broad distribution of phenolic group. FA sub-fractions also exhibited roughly two phenolic hydroxyl groups per every 1–3 phenyl rings. Differential absorbance spectra (DAS) derived Gaussian bands were associated to the inter-chromophore interactions, the changes of molecular conformations and functional groups with copper addition. Differential spectra slopes (DSlope275-295&325-375 ) were more significant with higher copper concentration and copper amounts bonded to carboxylic groups. UV–Vis and fluorescence spectra with 2D heterospectral COS revealed the copper binding heterogeneities and sequential orders of chromophores and fluorophores, quantitatively confirming by the order of conditional stability constants (log K Cu : 4.64–5.56). Salicylic-/polyhydroxyphenolic, hydroxyl and amino groups were strongly associated to the basic units for fluorophores. Sequential changes followed the order of humic-like→fulvic-like materials for FA3 /FA5, humic-like→fulvic-like→tryptophan-like materials for FA7, and humic-like→tryptophan-like→fulvic-like→tyrosine-like materials for FA9 /FA13 . Spectroscopic techniques combined with various models (especially for 2D COS) are beneficial to elucidate the binding heterogeneity and sensitivity for metal-organic matters at the functional group level. Graphical abstract: Image 1 Highlights: Average content of carboxylic/phenolic group and p Ka values of FAs were established. Roughly two phenolic hydroxyl groups per every 1–3 phenyl rings for sub-fractions. Salicylic/polyhydroxyphenolic/hydroxyl/amino groups were likely fluorophore units. DSlope were more significant with higher copper amounts bonded to carboxylic groups. Humic-like materials responded fastest to Cu than other chromophores/fluorophores. Abstract : Main findings of the work: The salicylic, polyhydroxyphenolic, hydroxyl and amino groups were likely the fluorophore units, and the humic-like materials responded fastest to copper binding for FA sub-fractions.